(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Hrydzhuk O. The most important aspects of language learning of the students of the Forestry training direction. In the article the feasibility of deepening the language training of the students of the Forestry University is substantiated; the main aspects of this process (terminologycal, lexicographic, grammar and stylistic, professionally-applied) are described; the ways of processing forestry and woodworking terminology are identif ied.